Exploring menopausal dynamics: a cross-sectional analysis of age, symptomatology, and sociodemographic influences in a developing population of women aged 40-60 - Engindeniz, Fatma Tuba; Erturk, Anıl; Aytekin, Necla (The European Research Journal, 2024)
Objectives: Menopause, a biological milestone, marks a pivotal phase in women’s lives characterized by ovarian function cessation and age-related changes. Our objective was to investigate menopausal symptoms and knowledge among women aged 40-60 years. Methods: This cross-sectional epidemiological study was conducted between June 1 and September 30, 2005, in the Nilufer Public Health Education and Research Area (NPHERA) region, aimed to assess menopausal symptoms and their correlates among 1013 women aged 40-60. The individuals included in the study were selected through a systematic sampling method, stratified by neighborhood weights and age groups based on the NPHERA 2004 Work Report and regional data, as well as information from the Health Centers Information System (HCIS), where the Electronic Health Records (EHR) are registered. Results: The mean age of natural menopause was found to be 46.7±4.8 years, showcasing sociodemographic factors’ influence. Postmenopausal women experienced higher rates of symptoms, with physical and mental exhaustion (82.8%), irritability (78.4%), and depressive mood (76.4%) prevailing. Logistic regression revealed that employment status significantly influenced menopausal status. Moreover, the age at menopause correlated positively with the age of the woman’s mother. Conclusions: This study contributes insights into menopausal experiences in developing countries, emphasizing the need for tailored healthcare approaches. Longitudinal investigations are warranted to comprehensively understand these associations and enhance women’s quality of life during menopause.